KEKAYAAN JENIS PORTUNIDAE DI SISI SHIPPING LINE SELAT MADURA - Bambang Irawan; Agoes Soegianto (The East Java Biological Society, 2006)
A monitoring activity for the existence of portunid crabs in the narrowest part of Madura Strait has been done from 2001 to 2004. Crabs have been collected in June or July each year in day time during spring tide. Crab collection was carried out in four sampling station (I to IV) using 0,5 cm trawl net for 10 minutes netting in each time. The results show that during four year monitoring six species of portunid crab has been captured. Among the six species three of them, Charybdis affinis, C. anisodon, and Portunus pelagicus were collected each year even with difference level in local distribution. C. affinis and P. pelagicus have been monitored in the same three stations, and C. anisodon has also been monitored in three stations but differs from other three portunid crab species, C. annulata. P. trituberculatus, and Scylla paramamosain were very rare and have been captured in less then three sampling times collection. We conclude that in this area the portunid crab has been dominated by C. affinis which have less economic value, and for C. anisodon even the number higher than other portunid genus the occurrence is not stabil as in C. affinis.